Efficacy and safety of olaparib combined with abiraterone in patients with metastatic castration-resistant prostate cancer: a systematic review and meta-analysis of randomized controlled trials - Luo, Zhanyang; Zhu, Bukun; Xu, Hong; Chen, Lixin; Song, Xiaoyun; Wang, Yu; Wang, Rui; Zheng, Jinzhou; Qiu, Yunhua; Yang, Jianfeng; Shi, Youyang (Frontiers in Oncology, 2023)
Background Olaparib has been proven for the treatment of metastatic castration-resistant prostate cancer (mCRPC). This meta-analysis aims to comprehensively evaluate the efficacy and safety of the combination of olaparib and abiraterone in patients with mCRPC. Methods The literature in PubMed, Embase, and Cochrane Library up until April 27, 2023, was systematically searched. In the studies included in this meta-analysis, olaparib combined with abiraterone was compared with abiraterone combined with placebo. Results Two randomized controlled trials involving a total of 938 patients were included. Analysis indicated that olaparib combined with abiraterone significantly prolonged radiographic progression-free survival (rPFS: relative risk [RR] 0.66, 95% confidence interval [CI] 0.55–0.79), time to secondary progression or death (PFS2: hazard ratio [HR] 0.72, 95% CI 0.56–0.93), time to first subsequent therapy or death (TFST: HR 0.75, 95% CI 0.63–0.89), time to second subsequent therapy or death (TSST: HR 0.73, 95% CI 0.58–0.93), and confirmed prostate-specific antigen (PSA) response (RR 1.14, 95% CI 1.05–1.24). However, no statistically significant differences were found in the overall survival (OS: HR 0.87 95% CI 0.70–1.09), objective response rate (ORR: RR 0.97, 95% CI 0.70–1.33), and incidence of total adverse events (RR 1.07, 95% CI 0.94–1.22). A notable detail that the combination of olaparib and abiraterone was associated with an increased incidence of high-grade anemia (RR 7.47, 95% CI 1.36–40.88). Conclusion Olaparib combined with abiraterone is effective for patients with mCRPC. However, combination therapy has treatment-related adverse events compared with monotherapy, and this could be improved in future treatment management. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023432287.